Cationic microporous polymer networks by polymerisation of weakly coordinating cations with CO2-storage ability - Fischer, Sabrina; Schimanowitz, Aneta; Dawson, Robert; Senkovska, Irena; Kaskel, Stefan; Thomas, Arne (Journal of Materials Chemistry A, 2014)
Microporous organic polymer networks with weakly coordinating cations in their backbone have been synthesised by metal catalysed C-C bond forming reactions. A functionalised tetraphenylphosphonium ion was synthesised and successfully used as a tecton in a co-polymerisation with tetrakis(4- bromophenyl) methane using nickel catalysed Yamamoto coupling and with triethynylbenzene in a palladium catalysed Songashira-Hagihara reaction. The microporous materials showed an apparent BET surface area of 1455 m2 g-1 and 540 m2 g-1, respectively. The Yamamoto product provide a CO2 uptake of 2.49 mmol g-1 at 273 K and 1 bar. After ion exchange with chloride CO2 uptake is further increased to 2.85 mmol g-1. This journal is © the Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-20